The Effect of Profitability and Leverage on Firm Value With ESG Disclosure as a Mediating Variable in Coal, Metal and Mineral Sub-Sector Companies - Anindya Cresentia Bariq; Krisdiana (Indonesian Journal of Business Analytics, 2026)
This study aims to determine the influence of profitability and leverage on firm value mediated by ESG Disclosure in mining companies in the coal, metal, and mineral sub-sector listed on the Indonesia Stock Exchange for the 2020-2024 period. The data used is secondary data from the annual financial statements and sustainability reports. This study uses descriptive and verifiable methods. The sample used was purposive sampling with a total of 14 companies that met the criteria for the 2020-2024 research period. The analysis technique used Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the help of SmartPLS software. The results of the study show that profitability has a positive and significant effect on the firm value, while leverage does not have a significant effect on the firm value. Profitability has no significant effect on ESG Diclosure, while leverage has a significant effect on ESG Diclosure. Furthermore, ESG Diclosure does not have a significant effect on the firm value. The results of the mediation test showed that ESG Diclosure was unable to mediate the influence of profitability and leverage on the firm value. The findings of this study show that the value of mining sector companies is more influenced by financial performance, especially profitability, than by ESG practices. In addition, ESG has not acted as a mediation mechanism between profitability and leverage on firm value. This research is expected to contribute to the development of the literature and become a consideration for management and investors.